Laparoscopic nephrectomy with single-portal access Sitracc® in swines - Meyer,Fernando (2012)
PURPOSE: To analyze the viability of using SITRACC® (single-portal access) to make partial or total nephrectomy in pigs and also to describe the technical difficulties found during these surgical procedures. METHODS: Ten pigs (Landrace specie) with 20kg in average were distributed in two groups: Group A - total right nephrectomy - and Group B - partial left nephrectomy -. The anesthetic procedure was initially done with thiopental (10mg/kg) and maintained with halothane. The surgical procedures were performed inside the Surgical Technique Room from Pontifical Catholic University of Parana (PUCPR). RESULTS: It was analyzed the surgery duration, time to insert SITRACC®, the volemic loss and the size of the organ. In the first surgeries, the surgical time and blood volume loss were higher (between 15 to 43 minutes and 120 to 400 mL, respectively). The more the procedure was performed, the more the surgeons were used to the technique, so the bleeding and the time of surgery was significantly reduced to 15 minutes and 50 mL of blood loss, respectively. The difficulties found were associated with the nippers, however that was not relevant for the surgical technique. It was also found that the intra-body suture caused an expressive volemic loss. CONCLUSION: The total and partial nephrectomy through umbilical single-access by using SITRACC® was feasible and safe in pigs.